Antibacterial Activity of Verticillin D Produced by Endophyte Clonostachys Rosea EC 28 - Dominique , Sagou; Alex, Pakora Gilles; Yeo, Dodehe; David, N’Guessan Jean (European Journal of Applied Sciences, 2022)
The objective of this work was to determine the antibacterial effect of endophytic fungi of Ceiba pentandra and to identify the compound(s) responsible for this activity. The antibacterial screening of the mycelium of endophytic fungi isolated from the bark of C. pentadra was evaluated against multiresistant strains E. coli and S. aureus. This screening led to the selection of isolate EC 28 for its ability to effectively inhibit the growth of the bacterial strains tested. Analysis of morphological characters and ITS rDNA sequences identified EC 28 as Clonostachys rosea. EC 28 was cultivated and extract. From the crude extract, two compounds, ergosterol and verticillin D, were isolated and identified. The in vitro activity of each compound against the growth of five strains bacterial multiresistant were assessed. Ergosterol did not have any activity. Verticillin D was active on all strains of bacterial multiresistant E. coli 942, E. coli 4814, S. aureus 931, S. aureus 934, and K. pneumonia 815 with respective MICs of 18.75; 18.75; 18.75; 3 and 37.5 µg/ ml.